An Asset-Focused Health Needs Assessment in a Rural Community in North India - Kaaren R. Mathias; Joseph M. P. Mathias; Philip C. Hill (Asia-Pac. J. Public Health, 2015)
Introduction. Health needs assessment (HNA) targets health resources to needs yet is rarely used in low-resource contexts such as the Indian villages. Methods. The authors combined rapid participatory appraisal (RPA) and HNA tools into 4 steps: (a) define HNA parameters, objectives, and community; (b) describe community demographics, health status, felt needs, assets, and health services; (c) analysis; and (d) design interventions considering felt needs, assets, impact potential, and organizational resources. Results. Community felt needs focused on lack of access to personal health services. Major morbidities included respiratory and diarrheal disease and maternal/child health problems. Formal anthropometry revealed high prevalence of underweight and stunting. Community assets included high land ownership, educated unmarried women, and operational government services. Conclusions. In low-resource developing country contexts with poor information systems, HNA is possible and useful. Including RPA and community participation to also assess assets resulted in programs responding to communities' needs using existing resources.
Keywords: Financial catastrophes; Impoverishment; Utilization of health care; Health insurance; inequalities